On the Generation of an Unseasonal EPB Over South East Asia. Issue 2 (20th February 2021) - Currie, J. L.; Carter, B. A.; Retterer, J.; Dao, T.; Pradipta, R.; Caton, R.; Groves, K.; Otsuka, Y.; Yokoyama, T.; Hozumi, K.; Le Truong, T.; Terkildsen, M.
Abstract: An unseasonal equatorial plasma bubble (EPB) event over South‐East Asia was observed on July 22, 2014 that has not been studied before. An investigation into this event is presented with the 26th July, 2014 as a comparison, non‐bubble day. The 22nd July EPB event occurred in the late post‐sunset sector and was associated with a small upward plasma drift. This event was highlighted using a new filter on the SCINDA S4 data. Ionosonde data show that sporadic E was present during the growth period for the EPB event. Modeling results from Thermosphere‐Ionosphere Electrodynamics (TEC) Global Circulation Model were used to conduct a numerical experiment investigating the direct effect of sporadic E on the linear R‐T growth rate. It was shown that sporadic E located in the correct latitude and local time can increase the linear growth rate. The seeding conditions were investigated using TEC data from Patumwan, Thailand. Wave‐like structures were observed for both days of interest, with larger amplitudes on 22nd July compared with the 26th July. Finally, simulations using the high‐resolution model PBMOD showed that for forcing from above conditions similar to the days of interest, EPBs would form in the presence of large seed perturbations. Therefore, it is likely that this unseasonal event was caused by large seed perturbations in TEC. Key Points: An unseasonal equatorial plasma bubble (EPB) over South‐East Asia is investigated and compared with a non‐EPB day Forcing from above conditions are not able to explain the EPB event Seeding perturbations in electron density are a likely candidate to explain the EPB event